Grepafloxacin Clinical Program for Lower Respiratory Tract Infections - Arne C Rodloff (Canadian Journal of Infectious Diseases)
The present paper evaluates the clinical trial program in lower respiratory tract infections treated with a new fluoroquinolone antibiotic, grepafloxacin. Unlike older quinolones, grepafloxacin has excellent activity against Gram-positive organisms, which include Streptococcus pneumoniae and “atypical” pathogens Legionella species. Mycoplasma pneumoniae and Chlamydia pneumoniae. Grepafloxacin has a long half-life of 12 to 15 h, which allows once daily dosing. Six studies have been conducted regarding community-acquired lower respiratory tract infections (LRTls), four about community-acquired pneumonia (CAP) and two about acute bacterial exacerbations of chronic bronchitis (ABECB) . In these studies, grepafloxacin demonstrated clinical equivalence with standard therapies. but, in patients with documented infections. grepafloxacin was statistically superior to amoxycillin in both CAP and ABECB. The new fluoroquinolone has a good safety profile, comparable with that of ciprofloxacin. The most common adverse effects of grepafloxacin were nausea and a metallic taste; however, these effects resulted in only a few discontinuations of therapy. With the increasing prevalence of resistance in pathogens isolated from community-acquired LRTIs, grepafloxacin offers a good alternative for monotherapy in these patients.